Development of Electronic Modules (E-Module) Assisted by Book Creator in Science Learning with Critical Thinking Skills Activities for Junior High School Students - Listiyorini; Leni Marlina; Muhamad Yusup (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to enhance students' critical thinking skills on the topic of substances and their changes using Book Creator. The research employed the Rowntree development model, with the research subjects being students at SMPN 1 Air Kumbang, Banyuasin Regency. The method used in this study was research and development (R&D) with the Rowntree development model and Tessmer evaluation, tested on 100 junior high school students. The results showed very high validity, with a Content Validity Index (CVI) and a Content Validity Ratio (CVR) of 0.8333, classified as very high. In the One-to-One evaluation stage, the practicality test results showed a percentage of 96.3% for the usefulness aspect and 91.67% for the ease-of-use aspect. In the Small Group Evaluation stage, the practicality of the e-module reached 97.53% for usability, classified as very practical, and 91.67% for ease of use. These results indicate that the e-module is considered very practical. The field test stage was conducted on 100 seventh-grade students to assess the effectiveness of the e-module in improving critical thinking skills. The results showed an N-Gain score of 56.11%, categorized as moderately effective. These findings indicate a significant improvement in students' critical thinking skills using Book Creator.